2009
DOI: 10.1111/j.1749-6632.2009.04043.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phosphorylation of Occludin and Tricellulin by CK2 and CK1

Abstract: In epithelial and endothelial cell layers tight junctions form selective apicolateral paracellular barriers separating luminal and extracellular spaces from the underlying tissues. Within the tight junctions the tetraspan transmembrane proteins occludin, claudins, and tricellulin form anastomosing strands of protein complexes, which interconnect opposing membranes of neighboring cells. Phosphorylation of tight junction components is critically involved in the regulation of tight junction assembly, maintenance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 19 publications
(34 reference statements)
0
43
0
Order By: Relevance
“…Introduction. Studies in other epithelia and bloodtissue barriers have demonstrated that the phosphorylation status of integral membrane proteins, peripheral adaptors/kinases/phosphatases, and/or scaffold proteins at the AJ (e.g., N-catenin, ␤-catenin) (Gumbiner, 2000;Dejana et al, 2008), TJ (e.g., occludins, claudins) (Cheng and Mruk, 2002;Gonzá lez-Mariscal et al, 2008;Dörfel et al, 2009;Findley and Koval, 2009;Raleigh et al, 2011), gap junction (e.g., Cx43, keratins) (Magin et al, 2007;Hesketh et al, 2009;Solan and Lampe, 2009;Maeda and Tsukihara, 2011), and desmosome (e.g., desmocollins, desmogleins, plakoglobin) (Aoyama et al, 2009;Thomason et al, 2010;Lie et al, 2011a) play a critical role in determining adhesive function at the cell-cell interface. The phosphorylation status of these proteins and their peripheral adaptors/regulators is regulated by nonreceptor protein kinases and/or lipid kinases in response to changes in the environment, growth and development, growth factors, cytokines, inflammation, infection, and oxidative stress (Cheng and Mruk, 36 CHENG AND MRUK 2002;Hawkins and Davis, 2005;Xia et al, 2005a;Suzuki and Hara, 2011).…”
Section: Nonreceptor Protein Kinases: Focal Adhesionmentioning
confidence: 99%
“…Introduction. Studies in other epithelia and bloodtissue barriers have demonstrated that the phosphorylation status of integral membrane proteins, peripheral adaptors/kinases/phosphatases, and/or scaffold proteins at the AJ (e.g., N-catenin, ␤-catenin) (Gumbiner, 2000;Dejana et al, 2008), TJ (e.g., occludins, claudins) (Cheng and Mruk, 2002;Gonzá lez-Mariscal et al, 2008;Dörfel et al, 2009;Findley and Koval, 2009;Raleigh et al, 2011), gap junction (e.g., Cx43, keratins) (Magin et al, 2007;Hesketh et al, 2009;Solan and Lampe, 2009;Maeda and Tsukihara, 2011), and desmosome (e.g., desmocollins, desmogleins, plakoglobin) (Aoyama et al, 2009;Thomason et al, 2010;Lie et al, 2011a) play a critical role in determining adhesive function at the cell-cell interface. The phosphorylation status of these proteins and their peripheral adaptors/regulators is regulated by nonreceptor protein kinases and/or lipid kinases in response to changes in the environment, growth and development, growth factors, cytokines, inflammation, infection, and oxidative stress (Cheng and Mruk, 36 CHENG AND MRUK 2002;Hawkins and Davis, 2005;Xia et al, 2005a;Suzuki and Hara, 2011).…”
Section: Nonreceptor Protein Kinases: Focal Adhesionmentioning
confidence: 99%
“…Phosphorylation of E-cadherin by KC1A inhibits its localization to cell contacts, negatively regulating cell adhesion (34). In addition, KC1A can phosphorylate occludin in vitro, but the functional significance of this is unknown (35). ASPP2 (apoptosis stimulating of 53 protein 2) (Fig.…”
Section: Specific Proteins Are Differentially Tagged In Cells Expressmentioning
confidence: 99%
“…Occl is phosphorylated by different protein kinases on serine, threonine and tyrosine residues (for a review, see Dörfel and Huber, 2012). Typical kinases are conventional Ca 2+ dependent and novel diacylglycerol dependent kinases (Andreeva et al, 2006), CK1, CK2 (Dörfel et al, 2009), c-Src (Kale et al, 2003), c-Yes (Chen et al, 2002) and activated, phosphorylated ERK 1 (extracellular signal related kinase) (Basuroy et al, 2006). Marchiando et al found that Occl is involved in the maintenance of the barrier function in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal domain appears to be involved in directing Tric to tricellular contacts. Despite this homology, Occl and Tric are differentially phosphorylated in their C-terminal tails (Dörfel et al, 2009). Tric severely influences TJ organization not only at tricellular contacts but also at the level of bicellular TJs.…”
Section: Introductionmentioning
confidence: 99%